Survey on Cloud Based IP Traceback Authentication Framework (International Journal of Engineering and Computer Science, 2018)
IP traceback is used to find network traffic attack. Origin of IP packet is not authenticated. So source of  IP  address is not trusted. A time limited token based authentication framework for authenticating traceback service queries is implemented. The design objective of the framework is preventing the illegal users for accessing traceback information.Thus to prevent network traffic attack